Associations between body height and cardiovascular risk factors in women and men: a population-based longitudinal study based on The Tromsø Study 1979–2016 - Kristin Benjaminsen Borch; Tom Wilsgaard; Inger Njølstad; Anne Helen Hansen; Sondre Haakonson Arntsen (BMJ Open)
Objectives Investigate associations between body height and cardiovascular disease risk factors at several time points in women and men across educational levels in Norway.Design Population-based longitudinal study.Setting The Tromsø Study, a population-based study with six surveys conducted between 1979 and 2016 in the municipality of Tromsø, Norway.Primary and Secondary Outcome Measures Body height, systolic blood pressure, diastolic blood pressure, serum total cholesterol, high-density lipoprotein (HDL) cholesterol, triglycerides and self-reported educational level.Participants 23 512 women and men (49.6% women), aged 30–49 years at first participation in The Tromsø Study. Participants who attended more than one survey contributed with repeated measurements for blood pressure and lipids.Blood pressure and lipid values were used as dependent variables in sex specific age-adjusted linear mixed models. Body height at first participation was the independent variable, while survey time point and educational level were used as covariates.Results Overall effect models showed inverse associations between body height and systolic blood pressure (reg. coefficients: −0.88 (95% CI –1.1, −0.6)), diastolic blood pressure (−0.41 (95% CI –0.6, –0.3)), serum total cholesterol (−0.12 (95% CI –0.1, –0.1)) and triglycerides (−0.06 (95% CI –0.1, –0.0)) in women. Inverse associations between body height and lipid variables were also observed in men (serum total cholesterol: −0.12 (95% CI −0.1, –0.1) triglycerides −0.05 (95% CI –0.1, –0.0)). Regression coefficients for associations between body height and cardiovascular risk factors varied across surveys. Overall, there were no associations between body height and cardiovascular risk factors based on educational level and survey.Conclusion The overall effect models support previous findings of inverse associations between body height and cardiovascular risk factors in women, and inverse associations between body height and lipids in men. Our study showed varied degrees of associations between body height and cardiovascular risk factors at different time points in Norway.